Analysis of n(87Sr)/n(86Sr), δ88Sr/86SrSRM987 and elemental pattern to characterise groundwater and recharge of saline ponds in a clastic aquifer in East Austria. Issue 2 (4th March 2019) - Tchaikovsky, Anastassiya; Häusler, Hermann; Kralik, Martin; Zitek, Andreas; Irrgeher, Johanna; Prohaska, Thomas
ABSTRACT: Elemental and isotopic pattern of n ( 87 Sr)/ n ( 86 Sr) and δ 88 Sr/ 86 SrSRM987 were used to characterise groundwater and recharge of saline ponds in a clastic aquifer in East Austria. Therefore, shallow, artesian and thermal groundwaters of the investigated aquifer along with rainfall and rivers were analysed using (MC) ICP-MS. The n ( 87 Sr)/ n ( 86 Sr) ratio and elemental pattern changed with aquifer depth as a result of progressing bedrock leaching and dissolution with increasing groundwater residence time. The n ( 87 Sr)/ n ( 86 Sr) ratio of shallow groundwater below saline ponds of 0.71019 ± 0.00044 was significantly different from thermal groundwater of 0.71205 ± 0.00035 ( U, k  = 2). In contrast to previous theories, this result suggested no recharge of saline ponds by upwelling paleo-seawater. Isotope pattern deconvolution revealed that rainfall accounted to about 60% of the n ( 87 Sr)/ n ( 86 Sr) ratio of shallow groundwater below saline ponds. The δ 88 Sr/ 86 SrSRM987 values of groundwater decreased from about 0.25 ‰ in most shallow, to predominantly negative values of about –0.24 ‰ in artesian groundwater. This result indicated leaching and dissolution of weathered minerals. In turn, the δ 88 Sr/ 86 SrSRM987 of deep thermal groundwater showed positive values of about 0.12 ‰, which suggested removal of 86 Sr from solution by carbonate precipitation. These results highlight the potential of δ 88 Sr/ 86 SrSRM987 signature as an additional geochemical tracer.